2017
DOI: 10.1002/ange.201710529
|View full text |Cite
|
Sign up to set email alerts
|

A Six‐Oxidase Cascade for Tandem C−H Bond Activation Revealed by Reconstitution of Bicyclomycin Biosynthesis

Abstract: As acommercial antibiotic,bicyclomycin (BCM) is currently the only knownn atural product targeting the transcription termination factor rho.Itbelongs to afamily of highly functionalizedd iketopiperazine (DKP) alkaloids and bears aunique O-bridged bicyclo[4.2.2]piperazinedione ring system, aC 1t riol, and terminal exo-methylene groups.W eh ave identified and characterized the BCM biosynthetic pathway by heterologous biotransformations,i nvitro biochemical assays, and one-pot enzymatic synthesis.AtRNA-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…This unambiguously confirmed that this was the BCM biosynthetic gene cluster. Our result agrees with those of recent studies by Patteson et al ( 32 ) and Meng et al ( 33 ) who, in parallel with our study, have reconstituted in vitro the functions of the CDPS and the oxidative steps in the S. cinnamoneus pathway.…”
Section: Resultssupporting
confidence: 94%
“…This unambiguously confirmed that this was the BCM biosynthetic gene cluster. Our result agrees with those of recent studies by Patteson et al ( 32 ) and Meng et al ( 33 ) who, in parallel with our study, have reconstituted in vitro the functions of the CDPS and the oxidative steps in the S. cinnamoneus pathway.…”
Section: Resultssupporting
confidence: 94%
“…NRPSs, for example, are traditionally considered to be nature's go-to machinery for catalysing amide bond formation independently of the ribosome during NP biosynthesis, but in recent years, many pathways have been characterized that employ alternative strategies for assembling amino and carboxylic acid substrates 182,183 . Examples include a transglutaminase homologue that catalyses N-acyl-β-peptide link formation during andrimid (36) biosynthesis in various γ-proteobacterial species 184 , the use of ATP-grasp enzymes such as that involved in the assembly of the β-lactone belactosin (37) 185 and cyclodipeptide synthases that utilize activated aminoacyl-tRNAs to biosynthesize diketopiperazine NPs, such as bicyclomycin (38) [186][187][188] . Indolmycin (39) is a potent antibacterial compound produced by various bacteria that is derived from the condensation of two nonproteinogenic amino acids, indolmycenic acid and D-4,5-dehydroarginine.…”
Section: Pathways Lacking Signature Biosynthetic Genesmentioning
confidence: 99%
“…Therefore, we sought to identify additional DKP dimerases through sequence similarity network (SSN) analysis. 23 Using NascB and NznB as in silico probes, along with known DKP functionalizing P450s from the thaxtomin (12), 24 pulcherrimic acid (13), 25 guanitrypmycin (14), [26][27][28][29] bicyclomycin (15), 30,31 and mycocyclosin (16) 32, 33 BGCs, we mined the NCBI database to identify candidate DKP dimerases. The resulting sequences were assembled into a SSN, which revealed a series of nodes clustered with NascB and NznB.…”
mentioning
confidence: 99%